2003
DOI: 10.1007/s00221-003-1442-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity in the substantia nigra in the anaesthetized rat has fractal characteristics. Evidence for firing-code patterns in the basal ganglia

Abstract: Current models of the basal ganglia assume a firing-rate code for information processing. We have applied five complementary computing methods to assess firing patterns in 188 cells of the substantia nigra in the anaesthetized rat. Fractal firing activity was found in 100% of nigral cells projecting to the superior colliculus, in 51% of cells projecting to the thalamus and in 33% of cells projecting to the pedunculopontine nucleus, but was practically absent in dopaminergic nigrostriatal neurons (3%). The find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…In attempts to move beyond traditional measures of neural coding and employ advanced tools from the signal processing world, spike trains have been analyzed for entropy (Strong et al, 1998) and fractal structure (Rodriquez et al, 2003; Goldberger et al, 2002). These measures have been used to explore the effects of apomorphine in Parkinson's patients (Rasouli et al, 2006), DBS in parkinsonian non-human primates (Dorval et al, 2008), and dopamine depletion in rats (Cruz et al, 2009).…”
Section: Spike Train Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In attempts to move beyond traditional measures of neural coding and employ advanced tools from the signal processing world, spike trains have been analyzed for entropy (Strong et al, 1998) and fractal structure (Rodriquez et al, 2003; Goldberger et al, 2002). These measures have been used to explore the effects of apomorphine in Parkinson's patients (Rasouli et al, 2006), DBS in parkinsonian non-human primates (Dorval et al, 2008), and dopamine depletion in rats (Cruz et al, 2009).…”
Section: Spike Train Analysesmentioning
confidence: 99%
“…Entropy is an indication of variability, based on the concept that some amount of variability in a time series is necessary to encode information (Strong et al, 1998; de Ruyter van Steveninck et al, 1997). Fractal dimension is an indication of the mathematical property of self-similarity, scale invariance or long range correlation (Rodriquez et al, 2003; Goldberger et al, 2002). The scaling exponent obtained in fractal analysis is an indication of the statistical properties or variability of a spike train.…”
Section: Spike Train Analysesmentioning
confidence: 99%
“…These states were shown not to be independent but, rather, linked by physical mechanisms that result in the observed fractal scaling. The impact of these findings can be appreciated from the profile of succeeding studies [85][86][87][88][89] on fractal kinetics from 1991 onwards. For example, in a recent work [89] it has been proved that patterns in spiking activity in suprachiasmatic nucleus neurons can be explained with the fractal point process model, which implies the presence of self-similarity in the profile of spike trains, proving thereby that no characteristic time scale dominates the dynamics of the spiking process.…”
Section: Fd-based Ion-channel Kinetics Studiesmentioning
confidence: 99%
“…Although MCA has been successfully implemented in different disciplines including psychology and health sciences (Bouilland and Loslever, 1998; Guinot et al, 2002; Meyer et al, 2004; Ambrogi et al, 2005; Almeida et al, 2009; Rennie and Roberts, 2009; Pinti et al, 2010; Avolio et al, 2013; Costa et al, 2013; Sagawa et al, 2013; Ayele et al, 2014; Touso et al, 2014), it is seldom encountered in neuroimaging literature. This method was applied here to study the functional connectivity of BG, centers which have shown multiple non-linear interactions in both animal and human studies (Rodriguez et al, 2003a,b; Marceglia et al, 2006; Schroll and Hamker, 2013). …”
Section: Introductionmentioning
confidence: 99%